Knowledge, attitude, and practice of non-medical students at Trisakti University about gingivitis and its prevention - Christina Beatrice; Albert (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Good oral health is related to general health. The prevention of periodontal disease has an impact on general health. 74% of Indonesians suffer from gingivitis, an early stage of infection of the gingiva when left untreated, can develop into periodontitis. The highest age category for gingivitis in Indonesia is 15-24 years and non-medical students are not exposed to oral health in their daily life. Objective: Evaluate the knowledge, attitude, and practice of non-medical students regarding gingivitis and its prevention. Materials and methods: A cross-sectional descriptive study was conducted by distributing a questionnaire consisting of 29 questions about knowledge, attitude, and practice regarding gingivitis and its prevention to 112 non-medical students from Trisakti University. Results: The study showed that 58.9%, 23.2%, and 17.9% of undergraduates had good, average, and poor knowledge respectively. Similarly, the majority of students had good attitude of 48.2%, followed by the average attitude of 47.3% of students and only 4.5% had poor attitude. However, the data depict that 47.3% had average level of practice, followed by good and poor practice with 38.4% and 14.3% respectively. Conclusion: The majority of non-medical students had good knowledge and attitude while in terms of practice were poor.